Classifying Metal Soil Concentrations with Bayesian Networks: Urban Background in the Southeastern United States - John F. Carriger; Robert G. Ford; Tim Frederick; Sydney Chan; Yuen-Chang Fung (Environmental Modeling & Assessment, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Research on biodeteriotration of plastics - Ji-Dong Gu; Tim Ford; Bryce Mitton; Ralph Mitchell (International Biodeterioration & Biodegradation, 2024)

Delineation of the complex microbial nitrogen-transformation network in an anammox-driven full-scale wastewater treatment plant - Pengfei Hu; Youfen Qian; Jinye Liu; Lin Gao; Yuxin Li; Yanbin Xu; Jiapeng Wu; Yiguo Hong; Tim Ford; Adi Radian; Yuchun Yang; Ji-Dong Gu (Water Research, 2023)

A solution for autonomous, adaptive monitoring of coastal ocean ecosystems: Integrating ocean robots and operational forecasts - David A. Ford; Shenan Grossberg; Gianmario Rinaldi; Prathyush P. Menon; Matthew R. Palmer; Jozef Skákala; Tim Smyth; Charlotte A. J. Williams; Alvaro Lorenzo Lopez; Stefano Ciavatta (Frontiers in Marine Science, 2022)
This study presents a proof-of-concept for a fully automated and adaptive observing system for coastal ocean ecosystems. Such systems present a viable future observational framework for oceanography, reducing the cost and carbon footprint of marine research. An autonomous ocean robot (an ocean glider) was deployed for 11 weeks in the western English Channel and navigated by exchanging information with operational forecasting models. It aimed to track the onset and development of the spring phytoplankton bloom in 2021. A stochastic prediction model combined the real-time glider data with forecasts from an operational numerical model, which in turn assimilated the glider observations and other environmental data, to create high-resolution probabilistic predictions of phytoplankton and its chlorophyll signature. A series of waypoints were calculated at regular time intervals, to navigate the glider to where the phytoplankton bloom was most likely to be found. The glider successfully tracked the spring bloom at unprecedented temporal resolution, and the adaptive sampling strategy was shown to be feasible in an operational context. Assimilating the real-time glider data clearly improved operational biogeochemical forecasts when validated against independent observations at a nearby time series station, with a smaller impact at a more distant neighboring station. Remaining issues to be addressed were identified, for instance relating to quality control of near-real time data, accounting for differences between remote sensing and in situ observations, and extension to larger geographic domains. Based on these, recommendations are made for the development of future smart observing systems.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Shu-Pei Cheng: A life-long pursuit for Environmental Science and Pollution Control - Tim Ford; Gary Cherr; Ji-Dong Gu (Ecotoxicology, 2021)

Preface - Ji-Dong Gu; Gary Cherr; Tim Ford (Ecotoxicology, 2021)

Increasing hydrologic variability threatens depleted anadromous fish populations - Eric J. Ward; Joseph H. Anderson; Tim J. Beechie; George R. Pess; Michael J. Ford (Global Change Biology, 2015)
Predicting effects of climate change on species and ecosystems depend on understanding responses to shifts in means (such as trends in global temperatures), but also shifts in climate variability. To evaluate potential responses of anadromous fish populations to an increasingly variable environment, we performed a hierarchical analysis of 21 Chinook salmon populations from the Pacific Northwest, examining support for changes in river flows and flow variability on population growth. More than half of the rivers analyzed have already experienced significant increases in flow variability over the last 60 years, and this study shows that this increase in variability in freshwater flows has a more negative effect than any other climate signal included in our model. Climate change models predict that this region will experience warmer winters and more variable flows, which may limit the ability of these populations to recover.

Effects of prazosin, clonidine, and propranolol on the elevations in brain reward thresholds and somatic signs associated with nicotine withdrawal in rats - Adrie W. Bruijnzeel; Mahendra Bishnoi; Irma A. van Tuijl; Kim F. M. Keijzers; Kate R. Yavarovich; Tim M. Pasek; Jenna Ford; Jon C. Alexander; Hidetaka Yamada (Psychopharmacology, 2010)

Semi-volatile organic compounds and trace elements in the Yangtze River source of drinking water - Bing Wu; Xuxiang Zhang; Xiaolin Zhang; Aishangjiang Yasun; Yan Zhang; Dayong Zhao; Tim Ford; Shupei Cheng (Ecotoxicology, 2009)

Special issue on source water risk control - Shupei Cheng; Tim Ford (Ecotoxicology, 2009)

Degradation of benzo(a)pyrene in Yangtze River source water with functional strains - Yan Zhang; Xuxiang Zhang; Bing Wu; Dayong Zhao; Mei Li; Yibin Cui; Tim Ford; Shupei Cheng (Ecotoxicology, 2009)

Class 1 integronase gene and tetracycline resistance genes tetA and tetC in different water environments of Jiangsu Province, China - Xuxiang Zhang; Bing Wu; Yan Zhang; Tong Zhang; Liuyan Yang; Herbert H. P. Fang; Tim Ford; Shupei Cheng (Ecotoxicology, 2009)

Rooting cuttings of Syringa vulgaris cv. Charles Joly and Corylus avellana cv. Aurea: the influence of stock plant pruning and shoot growth - Ross Cameron; Richard Harrison-Murray; Michael Fordham; Heather Judd; Yannick Ford; Tim Marks; Rodney Edmondson (Trees, 2003)